(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article analyzes the pedagogical significance of observation and laboratory activities in geography education, as well as their role in developing students’ scientific thinking, research skills, and professional competencies. The didactic potential of observation and experimental methods, along with the stages of their organization, is scientifically substantiated. The mechanisms of perception, analysis, and generalization of natural processes by students through practical activities are revealed. The study also justifies the effectiveness of studying complex geographical phenomena through modeling in laboratory conditions. Based on the findings, scientific and methodological recommendations aimed at improving practice-oriented and competence-based approaches in geography education have been developed.